PEMBERDAYAAN KADER POSYANDU MELALUI PENERAPAN METODE KONSELING GIZI DAN KOMUNIKASI EFEKTIF PADA KADER POSYANDU KELURHAN PADEMANGAN BARAT JAKARTA UTARA - Yulian Dinihari; Zakiah Fithah A'ini; Solihatun Solihatun (Universitas Muhammadiyah Ponorogo, 2019)
Kelurahan Pademangan Barat is one of the areas of malnutrition enclosed in the city of North Jakarta. Toddlers with malnutrition are recorded in the kelurahan. The level of education of the population as well as knowledge and public awareness in the field of health is relatively low suspected to be the main cause of the problem of malnutrition. One of the steps that can be done to help the nutritional problem is through nutrition counseling on posyandu cadres in the kelurahan. Nutrition counseling is a two-way communication process between counselor and client to help clients recognize and overcome nutritional problems. This program aims to increase knowledge of nutrition cadres of malnourished children under five. The outcomes of this program are the improvement of mother's nutritional knowledge and weight gain. Counseling was conducted several times, at each visit given by leaflet as a tool in delivering the material to the cadre. The visit time is approximately fifty hours. In addition, an informal mother and toddler approach is also used to identify parenting patterns, family characteristics, and children, as well as causes of malnutrition. As many as 88%,the cadre has increased the understanding and self confidence after following the nutrition counseling program.